Effectiveness of Group Counseling Services Using Assertive Techniques to Reduce the Physical Aggressive Behavior of Adolescents at the Medan High School - Widiasti, Wenny; Siregar, Alfin (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This research aims to analyze the effect of group counseling services using an assertive technical approach to reduce aggressive physical behavior among teenagers at Medan High School. This research uses quantitative research methods. This research uses a quasi-experimental pretest-posttest design. The sampling technique uses purposive sampling. The research location is Medan High School, which has a population of 70 class XI students. The samples were eight people from class XI IPS-1 and 8 XI IPS-2 students in the control group. The data collection technique uses a questionnaire; the data used in this research is a Likert scale with the data analysis technique using the T-test. This result is proven by data analysis, which obtained a percentage value for the experimental group from 84.7% to 72.8%, while for experimental group students, the percentage value obtained was 84.7% to 84.1%. The results of the independent samples t-test analysis also obtained a sig value equal to 0.029 < 0.05; it can be concluded that H0 is rejected and Ha is accepted in this research. These results can be interpreted as the influence of group counseling services using assertive techniques in reducing aggressive physical behavior among teenagers at Medan High School.